Research on architectural enhancements for integrating satellite into 5G networks - Wang Hucheng; Xu Hui; Sun Shaohui (Dianzi Jishu Yingyong)
Integration of satellite and terrestrial networks would bring better coverage, more flexible networking and more robust network architecture for 5G, which makes the 5G network connecting everything possible, and then becomes an important evolution direction for 5G network. This paper firstly introduces the necessity to support integration of satellite and terrestrial networks in B5G era, then analyses the developing phases and technical status of 5G network integrating with satellite from network architecture and technical standard point of view. Based on the technical status, the paper further analyses issues on system architecture evolution that 5G network integrating with satellite faces, and puts forward some architectural enhancement solutions, including 5G system enhancement on supporting satellite backhaul and User Plane Function(UPF) on-board.